Edukasi Masyarakat Dalam Upaya Pencegahan Penyebaran Covid-19 di Desa Bangun Sari - Tarita Aprilani Sitinjak (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2022)
Early 2020, the Covid-19’s pandemic hit Indonesia, causing many negative effects in social life. To prevent another negative effect from the Covid-19 pandemic, the community participant needed. Counseling is the form of the socializing the harm of Covid-19, implementation of health protocol and training to utilize the material that are around the community environment to made hand sanitizer. These are the implementation of community service activities to people in Bangun Sari village, Manuhing, Gunung Mas, Palangka Raya. These activities are collaboration between Universitas Palangka Raya and the government of Bangun Sari Village, involving KKNT-Mandiri students. The result of community service activities is the people of Bangun Sari Village understand the danger of Covid-19 virus, know how to prevent the infection of the virus, obedient to conduct the health protocols such as wearing mask, washing hand using hand sanitizer, and social distancing. The other result is people of Bangun Sari village gain the skill to produce the hand sanitizer by using herbal ingredient such as Betel leaf, lemon, water, and making the desinfectant.